Trascendencia, inmanencia y ritual: una nueva mirada a las novelas de Joan Perucho - Gregori, Alfons (Romanica Silesiana)
Catalan writer Joan Perucho, one of the most recognized Hispanic authors of fantasy literature, presents in his works experimental and avant‑garde subjects that are typical of the postmodern era. Nevertheless, his literary texts go far beyond parody and meaningless games. The main objective of this article is to analyse Peruchos’ novels taking into account the dichotomy between transcendence through believing — that is to say, strategies configured to transcend the spiritual void of the last century — and immanence understood, on the one hand, materially (as intertextual frames, forms, and procedures) and, on the other hand, culturally (as rituals related to law, moral, ethics, or gastronomy in the everyday life). Key words: fantasy literature, Joan Perucho, transcendence, immanence, ritual